The Impact of Brand Reputation, Brand Equity and Brand Competence on Brand Loyalty - Makatita, Muhajir; Amin, Mohamad; Surijadi, Herman (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2022)
The aims of this study were to test and analyze the impact of reputation, equity and brand competence to the handphone brand loyalty in Ambon city. The Population in this study were all the handphone users in Ambon City. The sampling technique used in this study was purposive sampling which took 75 respondents matched with the criteria. Multiple linier regression was used to analyze the data. The result showed that the variable of reputation, equity, and brand competence had positive and significant impact on the handphone brand loyalty in Ambon City. This can be proven through the regression coefficient of reputation, equity, and brand competence in which if the score of reputation, equity, and brand competence improves, the score of loyalty will also improve. Therefore, it can be said that the improvement of reputation, equity, and brand competence will improve the loyalty of handphone brand in Ambon City.